TINJAUAN KEMASAN PRODUK UMKM PADA DESTINATION BRANDING KOTA SOLO - Nidyah Widyamurti; Hermansyah Muttaqin; Jauhari; Sigied Himawan Yudhanto; Arif Ranu Wicaksono; Lalita Gilang (Jurnal Dimensi DKV Seni Rupa dan Desain, 2022)
Abstract  MSMEs’ Product Packaging Review on Solo’s Destination Branding. With its designation (Solo.red) as the City of Culture, Solo has a distinct image and its positioning on the Indonesian tourism map, which is very appealing if showcased on the packaging of its souvenir products.  MSMEs' processed food products are souvenirs that tourists find attractive when visiting a tourist destination. Packaging that promotes regional specialties commonly encourages tourists to purchase products. The product packaging can include storytelling about the areas visited, but this strategy is not used for all MSMEs' processed food products. The identification of design elements on the packaging and the literature study on how to package processed food according to government legality for processed food products of SMEs were performed in this study to investigate the implementation of the destination branding concept of Solo as a City of Culture on the packaging of souvenir products. It is expected that packaging labels developed with such a strategy empower MSMEs and support their products to become the spearheads in the tourism sector in Solo City.   Keywords: processed food products, packaging, MSMEs, destination branding   Abstrak Tinjauan Kemasan Produk UMKM pada Destination Branding Kota Solo. Dengan penetapan Kota Surakarta (Solo.red) sebagai Kota Budaya, Solo mempunyai citra khas dan positioning tersendiri dalam peta pariwisata Indonesia yang akan sangat menarik apabila ditampilkan dalam kemasan produk oleh-olehnya. Produk makanan olahan UMKM merupakan produk oleh-oleh yang cukup diminati wisatawan saat mengunjungi suatu destinasi wisata. Kemasan yang menampilkan kekhasan daerah seringkali mendorong pembelian produk oleh wisatawan. Kemasan produk bisa menampilkan storytelling atas daerah yang dikunjungi, tapi tidak semua produk makanan olahan UMKM dikemas dengan strategi demikian. Identifikasi atas elemen-elemen desain pada kemasan dan studi literatur tentang cara pengemasan makanan olahan sesuai legalitas pemerintah atas produk makanan olahan UMKM dalam penelitian ini dilakukan untuk melihat implementasi konsep destination branding Kota Solo sebagai Kota Budaya pada kemasan produk oleh-olehnya. Diharapkan, Label kemasan dengan strategi demikian akan membuat UMKM semakin berdaya dan produk mereka mampu menjadi ujung tombak dalam bidang pariwisata di Kota Solo. Kata kunci: produk makanan olahan, kemasan, UMKM, destination branding